Digital hygiene strategies for educational resilience - Dmytro Husiev; Hanna Sorokun (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In today’s rapidly evolving digital world, education is deeply intertwined with technology. Cyberculture, encompassing the social, cultural, and communicative aspects of digital interactions, shapes how knowledge is generated, shared, and assimilated. Meanwhile, digital hygiene – practices aimed at ensuring safety and well-being in online spaces – has become a critical shield against cyber threats. This integration is particularly vital in educational institutions, where students and educators increasingly rely on digital tools for learning, collaboration, and research. The educational process must adapt to these phenomena to promote not only academic success but also responsible digital citizenship. The relevance of this topic is underscored by global trends, such as Europe’s digital strategies and Ukraine’s initiatives for educational digitalization, including the "New Ukrainian School" reform [1]. Cyberattacks on educational institutions have surged, with a 258% increase reported in 2023 [2], highlighting the urgent need to integrate digital hygiene into curricula. Cyberculture encompasses the practices, norms, and artifacts emerging from digital technologies and virtual spaces. It extends beyond mere tool usage to include new forms of communication, creativity, and social interaction, such as digital art, online communities, and collaborative network projects. In education, cyberculture manifests through remote learning platforms, social media for knowledge exchange, and tools fostering global collaboration. Digital culture, a related concept, integrates socio-humanitarian and educational aspects, evolving from notions like "post-cyberculture" to emphasize virtual forms of cultural expression. Educators must view cyberculture as a dynamic force shaping teaching methods. For instance, employing digital narratives or gamified learning environments can boost engagement and foster cultural awareness in online interactions. However, without guidance, cyberculture can amplify issues like misinformation or digital divides. Thus education should cultivate digital literacy – skills for effectively using electronic tools – and digital competence, encompassing knowledge, attitudes, and ethical principles for smart technology use. This comprehensive approach ensures students not only navigate but also contribute positively to cybercultural spaces.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; educational resilience; cyberculture